Oncoplastic Surgery: Pushing the Limits of Breast‐Conserving Surgery. Issue 2 (12th February 2015) - Clough, Krishna B.; Benyahi, Djazia; Nos, Claude; Charles, Caroline; Sarfati, Isabelle
Abstract In recent decades, the surgical management of breast cancer has steadily and considerably improved. Mutilating procedures have given way to more individualized surgical approaches aiming to preserve the breast as much as possible. For large tumors, preoperative chemotherapy is a major tool, but emerging oncoplastic surgery techniques are also a new approach in the armamentarium of breast cancer surgery, as a third option between conventional breast‐conserving surgery and mastectomy. As this new treatment modality allows wider margin excision, it reduces the need for re‐excision procedures and possibly increases breast conservation rates by extending the indications of breast‐conserving surgery. This review will provide an overview of current practices and clinical data available to date on oncoplastic surgery.